The resilience of Chinese minorities: Transformation of Chinese entrepreneurs in Lasem batik industry, Central Java, Indonesia - Yesi Mekarsari; Mochamad Iqbal Jatmiko (SIMULACRA: JURNAL SOSIOLOGI, 2020)
The Lasem batik industry underwent a significant dynamic change after the inauguration of batik as an intangible cultural heritage by UNESCO on October 2, 2009. The increasing growth of the batik industry in Lasem turned out to affect the decline in industrial ownership by Chinese-Indonesian business person. Although the Chinese-Indonesian business person served as an initiator in the Lasem batik industry, it does not guarantee their survival against a massive ownership transition. This article explores the changing dynamics of the Lasem batik industry from the perspective of the Chinese-Indonesian business person who still maintains the continuity of their business. Employing a qualitative method and a narrative study approach, this article seeks to deepen the historical narrative about the lives of six Chinese-Indonesian business persons in the Lasem batik industry. The findings show that since post-reformation until now, the ownership of the Lasem batik industry by Chinese-Indonesian business person continues to decline. Therefore, the expansion of the intra-ethnic network, identity hybridization, cultural acculturation, and authentication of batik motifs became the survival strategies of Chinese-Indonesian business persons to be resistant to industrial ownership transitions and survived competing in theLasem batik business.